Co-localised phosphorus mobilization processes in the rhizosphere of field-grown maize jointly contribute to plant nutrition. (February 2022) - Bilyera, Nataliya; Hummel, Christina; Daudin, Gabrielle; Santangeli, Michael; Zhang, Xuechen; Santner, Jakob; Lippold, Eva; Schlüter, Steffen; Bertrand, Isabelle; Wenzel, Walter; Spielvogel, Sandra; Vetterlein, Doris; et al.
Abstract: Understanding phosphorus (P) dynamics in the rhizosphere is crucial for sustainable crop production. P mobilization processes in the rhizosphere include the release of plant and microbially-derived protons and extracellular phosphatases. We investigated the effect of root hairs and soil texture on the spatial distribution and intensity of P mobilizing processes in the rhizosphere of Zea mays L. root-hair defective mutant ( rth3 ) and wild-type (WT) grown in two substrates (loam, sand). We applied 2D-chemical imaging methods in custom-designed root windows installed in the field to visualize soil pH (optodes), acid phosphatase activity (zymography), and labile P and Mn fluxes (diffusive gradients in thin films, DGT). The average rhizosphere extent for phosphatase activity and pH was greater in sand than in loam, while the presence of root-hairs had no impact. Acidification was significantly stronger at young root tissue (<2 cm from root cap) than at older root segments (>4 cm from root cap) and stronger in WT than rth3. Accompanied with stronger acidification, higher P flux was observed mainly around young, actively growing root tissues for both genotypes. Our results indicate that acidification was linked to root growth and created a pH optimum for acid phosphatase activity, i.e ., mineralization of organic P, especially at young root tissues which are major sites of P uptake. Both genotypes grew better in loam than in sand; however, the presence of root hairs generally resulted in higher shoot P concentrations and greater shoot biomass of WT compared to rth3 . We conclude that soil substrate had a larger impact on the extent and intensity of P solubilization processes in the rhizosphere of maize than the presence of root hairs. For the first time, we combined 2D-imaging of soil pH, phosphatase activity, and nutrient gradients in the field and demonstrated a novel approach of stepwise data integration revealing the interplay of various P solubilizing processes in situ . Graphical abstract: Image 1 Highlights: In situ chemical imaging of pH, acid phosphatase activity, P and Mn flux in the rhizosphere of field grown maize. Average rhizosphere extents were larger in sand than in loam. Root hairs mostly did not increase rhizosphere extents of imaged parameters. Young root tissue of wild-type maize was more acidic than of root hair-defective mutant rth3 . Acidification from young root tissue created pH optimum for acid phosphatase activity and P uptake.